2012
DOI: 10.1186/1756-3305-5-67
|View full text |Cite
|
Sign up to set email alerts
|

First report of venereal and vertical transmission of canine leishmaniosis from naturally infected dogs in Germany

Abstract: BackgroundCanine leishmaniosis (CanL) is a zoonotic disease caused by Leishmania (L.) infantum. It is endemic to several tropical and subtropical countries but also to the Mediterranean region. It is transmitted by phlebotomine sandflies but occasional non-vector transmissions have been reported, including vertical and horizontal transmission.FindingsThe authors report a case of CanL in a female boxer dog from Dusseldorf, Germany, that had never been in an endemic region. A serum sample from the bitch was test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 19 publications
0
63
0
1
Order By: Relevance
“…54,58,65,67,150 The increasing evidence regarding the coital vertical transmission of L. infantum worldwide has highlighted the clinical importance of genital disease in the leishmanial dog. 14,103,133 Although the clinical or subclinical disease and genital pathology of the male dog in the form of orchitis, epididymitis, chronic prostatitis causing hematospermia-teratozoospermia, penile granulomatous disease, and balanoposthitis have been indisputably linked to CanL, it seems that L. infantum does not have genital tropism in the bitch. 38,82,92,134 However, coital transmission of the parasite could be achieved by the neoplastic cells of transmissible venereal tumor, a common stray dog disease in many countries.…”
Section: General Pathomechanismsmentioning
confidence: 99%
“…54,58,65,67,150 The increasing evidence regarding the coital vertical transmission of L. infantum worldwide has highlighted the clinical importance of genital disease in the leishmanial dog. 14,103,133 Although the clinical or subclinical disease and genital pathology of the male dog in the form of orchitis, epididymitis, chronic prostatitis causing hematospermia-teratozoospermia, penile granulomatous disease, and balanoposthitis have been indisputably linked to CanL, it seems that L. infantum does not have genital tropism in the bitch. 38,82,92,134 However, coital transmission of the parasite could be achieved by the neoplastic cells of transmissible venereal tumor, a common stray dog disease in many countries.…”
Section: General Pathomechanismsmentioning
confidence: 99%
“…Transmission occurs through the bite of sandflies infected with this protozoon (BARATA et al, 2004). However, vertical transmission (DUBEY et al, 2005;ROSYPAL et al, 2005;PANGRAZIO et al, 2009) and venereal transmission (NAUCKE & LORENTZ, 2012) should also be considered.…”
Section: Considerando a Falta De Estudos Sobre Lesões Nos óRgãos Genimentioning
confidence: 99%
“…Although it has not been proven that transmission actually occurred in utero, this report demonstrated that bitches with VL can be a source of infection for their pups under natural conditions. Naucke and Lorentz reported two cases of autochthonous VL in Germany [32]. A bitch that has never left a region in which there are no phlebotomine sand flies developed clinical VL.…”
Section: Importance Of Sexual and Vertical Transmission Of Vlmentioning
confidence: 99%